(untitled) (Philological Studies, 2019)
This paper discusses Macedonian light verb constructions (LVCs) with дава (give) in which the light verb дава (give) has undergone a metaphorical extension in the sphere of interpersonal communication. These LVCs are based on deontic verbs of communication and they indicate an attempt to change the behavior of another person. Sentences with these LVCs usually have near-synonymous parallels with corresponding full verbs (FVs), but LVCs are often preferred. Syntactic tests and quantitative analyses demonstrate that the main reasons for this are: the possibility for argument reduction in LVCs, the possibility for an alternative hierarchy of arguments, the possibility for quantification of the noun in LVCs, the possibility for adjectival modification of the noun within the LVC, the absence of complete synonymy between the LVC and FV.This paper discusses Macedonian light verb constructions (LVCs) with дава (give) in which the light verb дава (give) has undergone a metaphorical extension in the sphere of interpersonal communication. These LVCs are based on deontic verbs of communication and they indicate an attempt to change the behavior of another person. Sentences with these LVCs usually have near-synonymous parallels with corresponding full verbs (FVs), but LVCs are often preferred. Syntactic tests and quantitative analyses demonstrate that the main reasons for this are: the possibility for argument reduction in LVCs, the possibility for an alternative hierarchy of arguments, the possibility for quantification of the noun in LVCs, the possibility for adjectival modification of the noun within the LVC, the absence of complete synonymy between the LVC and FV.